Role of Supervisors in Improving Teacher's Ability to Conduct Class VI Fiqh Learning Processes in State Madrasah Ibtidaiyah 7 Langkat - Candra Wijaya; Tien Rafida; Darno Darno (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2019)
1) The implementationof the main tasks and functions of supervisors in guiding and guiding Class VIjurisprudence teachers in Madrasah Ibtidaiyah Negeri 7 Langkat refer to theMinister of Administrative Reform and Bureaucratic Reform No. 21 of 2010concerning Functional Position of School Supervisors and Numbers Credit, usingthe principle of sustainability with the aim of increasing the ability of teachers toimplement content standards, processes, graduate competencies, and assessments,2) In carrying out class VI Fiqh learning planning in state Madrasah Ibtidaiyah 7Langkat, Madrasah supervisors annually assess the teacher's ability to carry outplanning class VI Fiqh learning in State Madrasah Ibtidaiyah 7 Langkat.